Avaliação da atividade hepatoprotetora dos extratos etanólicos de Baccharis trimera e Morus nigra frente à indução de dano hepático em ratos Wistar - Cassanego, Gabriela Buzatti (2019)
The liver is a very versatile organ and isresponsible for maintaining body homeostasis. The role it exerts physiologically makes it vulnerable to the development of pathologies, being of great clinical relevance. Baccharis trimera (Less.) DC., popularly known as "carqueja" and Morus nigra Linnaeus, also called "amoreira-preta", are used by the population for the prevention and treatment of liver diseases, however their efficacy is not fully elucidated in the literature. The aim of the study was to perform the phytochemical analysis and to evaluate the potential hepatoprotective activity of the ethanolic extract of B. trimera (EFBT) and M. nigra (EFMN), against hepatic damage induced by thioacetamide. Thirty mice were used, divided into 5 experimental groups (n=6). The animals were pre-treated orally with 60 °GL solution, silymarin 50 mg/kg, EFBT 400 mg/kg and EFMN 1000 mg/kg, for three weeks. Induction of hepatic damage was induced by administering two doses of TAA 300 mg/kg intraperitoneallyon 20th and 21st days.To the control group, it was administered solution saline 0,9%. The chromatographic profile of the EFBT revealed epicatechin and apigenin as the major constituents of the EFBT. Rutin was the main compound found in the EFMN. The results showed that TAA induced liver damage by increasing the levels of enzymes AST, ALT, GGT and LF count, and reducing PT, PQ and PPT levels. The treatment with EFBT was able to reduce the levels of the AST and GGT enzymes, in addition to reducing the LF, and the treatment with EFMN significantly reduced only the levels of the GGT enzyme.The administration of EFBT normalized the body weight gain and consequently the liver weight of the previously treated animals when compared to the groups. The macroscopic and histopathological analyzes of the liver are in agreement with the results previously described for the study. It was observed that the administrations of the silymarin and EFBT reduced the lipoperoxidationin the hepatic tissue when compared to the TAA group. Therefore, we can conclude that the model of induction of hepatic damage using TAA, was effective in its purpose. The present investigation demonstrated that previous treatment with EFBT attenuated the liver damage caused by TAA, proving to be a promising natural source for pharmacological use. The administration of EFMN did not present significant results when compared to the silymarin and EFBT group, thus, it is necessary to perform more studies with the plant.